Ontario Kindergarten Teachers’ Social Media Discussions About Full Day Kindergarten - Lynch, Meghan (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2014)
This exploratory netnographic study describes how a sample of Ontario kindergarten teachers perceives the new Ontario Full Day Kindergarten (FDK) curriculum. Discussions from teacher message boards, the comment sections of online news articles, and interviews with kindergarten teachers were analyzed and coded using a qualitative approach. Analysis revealed three major themes: 1) Class size concerns, 2) Team teaching concerns, and 3) Play-based curriculum concerns. Results are in broad agreement with those reported in existing research into Ontario’s FDK initiative. Findings highlight the need for further research with educators involved in Ontario’s FDK and also contribute to the burgeoning field of netnography research. Suggestions for future research and practice are included.